Toxidez de alumínio em genótipos de Pfaffia glomerata (Spreng.) Pedersen e Pfaffia tuberosa (Spreng.) Hicken - Maldaner, Joseila (2008)
Al toxicity, especially in acid soils, is a determinant factor of lower productivity for several cultures and, although some studies have been developed to elucidate this problem, studies on medicinal plants are extremely rare. The aim of this study was to identify and characterize morphologic, physiologic and biochemical aspects of Al toxicity on two Pfaffia glomerata (BRA and JB/UFSM) accessions and one Pfaffia tuberosa access. Plantlets of three accesses were submitted to five Al concentrations (0, 50, 100, 150 e 200 mg L-1) in vitro and after 24 days several growth parameters were evaluated. Two accesses of P. glomerata were submitted to the same Al concentrations in a hydroponic system during 7 days, after which the growth and some biochemical parameters related to oxidatitive stress were evaluated. Under both conditions, Al concentrations higher than 100 mg L-1 affected most of the growth parameters of both P. glomerata accessions, whereas P. tuberosa was not affected. However, in vitro we verified an increase in growth for both P. glomerata accessions at 50 and 100 mg L-1 Al. In the hydroponic system, although the patterns of biomass production and roots elongation differ for the two accesses of P. glomerata, it was observed that the BRA access was more sensitive to Al toxicity than the JB/UFSM access. The Al concentration in root and shoot tissues increased with increasing Al in the substrate, however the increase was greater in the roots. Al triggered a more pronounced increase of lipid peroxidation in the BRA access. The H2O2 concentration in JB/UFSM roots decreased at 150 mg L-1 Al, however there was an increase of H2O2 in the shoot of both accesses. Al toxicity caused a greater change in catalase activity (CAT) in the roots than in the shoot. CAT activity in the roots of JB/UFSM increased at 50 and 200 mg L-1 of Al, while in the BRA access it decreased at all Al levels. As far as, both in the roots and shoots, the activity of ascorbate peroxidase (APX) was higher in the BRA access than in the JB/UFSM access. On the other hand, the decrease in superoxide dismutase (SOD) activity by Al exposure was greater in BRA than in JB/UFSM. In relation to the non enzymatic antioxidant system, there was an increase in ascorbic acid (AsA) in the roots of the BRA access and in the shoot of both accesses in the presence of Al. On the other hand, there was reduction in AsA concentration in the JB/UFSM roots. The concentration of non-protein thiol groups (NPSH) was reduced by Al in the roots of both accessions. NPSH concentration increased in the shoot of JB/UFSM in the presence of Al. On the other hand, in the BRA access there was an increase of NPSH at 100 mg L-1 Al, while there was a reduction at 50, 150 and 200 mg L-1. We conclude that the reduction in growth of both P. glomerata accessions, induced by Al, can be attributed to the increase of oxidative stress, and the JB/UFSM access has a more efficient antioxidant system than that of the BRA access for removing reactive oxygen species.